FOTO BERITA TENTANG KEMERDEKAAN REPUBLIK INDONESIA TAHUN 1945, KARYA ALEX MENDUR DAN FRANS MENDUR (ANALISA SEMIOTIKA KEBUDAYAAN KONTEMPORER, TEORI ARTHUR ASA BERGER) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research is entitled "Photo News About the Independence of the Republic of Indonesia in 1945, by Alex Mendur and Frans Mendur (Semiotic Analysis Contemporary Culture, Arthur Asa Berger's Theory) ". This study aims to find out what the meaning is contained in the photojournalism of the Independence of the Republic of Indonesia in 1945 with a semiotic theory approach Arthur Asa Berger and to find out what cultural values are there in three photojournalism on the independence photo of the Republic of Indonesia in 1945, as well to find out how the photojournalism of the independence of the Republic of Indonesia gives an impact or influence on the history of the nation's development theory used is the semiotic analysis of Arthur Asa Berger, namely how The signs that work or how signs are employed This study uses a descriptive-interpretive approach with the type of qualitative research. The object of this research is photojournalism about "Mendur Independence". The process of the Republic of Indonesia data collection was carried out in 1945 with Alex Mendur's technical works of literature and references, interviews, and documentation studies. Data were analyzed using techniques photo composition technique / ELDFAT method and photo-taking angle. The results of this study indicate that journalistic photos are about "The independence of the Republic of Indonesia in 1945, by Alex Mendur and Frans Snoring. Namely, photo 1 reading of the text of the Proclamation of Indonesian independence by. Soekarno, photo 2 of the raising of the Red and White Flag by Latief Hendraningrat assisted by S. Suhud and Sk Trinurti, and photo 3 of the atmosphere of the community ceremony watching the raising of the Red and White Flag. And there are cultural values in the three photos, namely, the value of power, the value of solidarity, and the value of art, as well as the three photos. very have an impact or influence on Indonesian independence in the present era.